Graphene K‐Tape Meshes for Densely Distributed Human Motion Monitoring. Issue 1 (6th December 2020) - Lin, Yun‐An; Zhao, Yingjun; Wang, Long; Park, Yujin; Yeh, Yi‐Jui; Chiang, Wei‐Hung; Loh, Kenneth J.
Abstract: Wearable sensors that measure parameters associated with physical activity and bodily motions have been regarded as an indispensable tool for assessing personal wellness. Recent advances in nanocomposite strain sensors have been successfully used for monitoring skin strains and other strain‐derived physiological parameters. This study complements the existing body of work and presents a flexible, self‐adhering, fabric‐based wearable sensor for measuring skin strains and human motions. Graphene nanosheet thin films are directly spray‐coated onto kinesiology tape (K‐Tape) to obtain a self‐adhering strain sensor of high sensitivity and linearity. Their stable sensing performance and high repeatability are verified, while human subject tests confirm that they adequately capture muscle engagement during functional movements. In addition, densely distributed strain monitoring can be achieved using an electrical impedance tomography measurement approach and algorithm. Spatial strain sensing is successfully demonstrated using a single strip of piezoresistive K‐Tape, as well as when a K‐Tape network or mesh pattern is formed. The results show promise for using graphene K‐Tape meshes to measure how specific major muscle groups engage during different physical activities. Abstract : This study introduces a method for capturing distributed muscle engagement and skin strains using flexible, self‐adhering, fabric‐based, wearable sensors. Strain‐sensitive graphene nanosheet thin films are integrated with kinesiology tape. An electrical impedance tomography measurement method and algorithm is employed to capture distributed strains in continuous and patterned sensors during different functional movements.